Combination of an allogenic and a xenogenic bone substitute material with injectable platelet-rich fibrin – A comparative in vitro study. (July 2020) - Kyyak, Solomiya; Blatt, Sebastian; Pabst, Andreas; Thiem, Daniel; Al-Nawas, Bilal; Kämmerer, Peer W
The aim of the in vitro study was a comparison of an allogenic (ABSM) and a xenogenic bone substitute material (XBSM) with and without injectable platelet-rich fibrin (ABSM-i-PRF & XBSM-i-PRF) on cell characteristics of human osteoblasts (HOB). Here, ABSM and XBSM (+ i-PRF = test; - i-PRF = control) were incubated with HOB for 3, 7 and 10 days. HOB viability, migration, proliferation and differentiation (RT-PCR on alkaline phosphatase (AP), bone morphogenetic protein 2 (BMP-2) and osteonectin (OCN)) were measured and compared between groups. At day 3, an increased viability, migration and proliferation was seen for ABSM-i-PRF. For viability and proliferation (days 7 and 10) and for migration (day 10), ABSM-i-PRF/XBSM-i-PRF showed higher values compared to ABSM/XBSM with maximum values for ABSM-i-PRF and minimum values for XBSM. At days 3 and 7, the highest expression of AP was detected in ABSM-i-PRF/XBSM-i-PRF when compared to ABSM/XBSM, whereas at day 10, AP expression levels were elevated in ABSM-i-PRF/ABSM. The highest BMP-2 expression was seen in ABSM-i-PRF whereas OCN expression showed higher levels in ABSM-i-PRF/XBSM-i-PRF at days 3 and 7 with lowest expression for ABSM. Later on, elevated OC levels were detected for ABSM-i-PRF only. In conclusion, i-PRF in combination with ABSM enhances HOB activity when compared to XBSM-i-PRF or untreated BSM in vitro. Therefore, addition of i-PRF to ABSM and – to a lower extent – to XBSM may influence osteoblast activity in vivo.